RESULTS OF THE STUDY OF THE UNIFORM DISTRIBUTION OF THE WORKING SUSPENSION BY SEED MASS AND THE COMPLETENESS OF THE TREATMENT - Kuliyev Tokhir Mamarajapovich; Jumaniyazov Qadam; Akramov Alisher Ashuraliyevich; Karimov Jakhongir Djumabayevich (Modern American Journals, 2025)
The efficiency of seed treatment with protective and stimulating agents significantly depends on the uniform distribution of the working suspension over the seed mass and the completeness of coverage. This study aimed to investigate the uniformity of suspension distribution during mechanized seed treatment and to evaluate the completeness of surface coverage under various operating conditions. Experiments were conducted using different types of treatment equipment and suspension formulations. The results demonstrated that optimal distribution depends on the physical properties of the suspension, seed geometry, and the dynamic mixing regime. Quantitative assessment showed that the coefficient of variation in the suspension distribution decreased with improved mixing technology and nozzle design. Furthermore, completeness of treatment was assessed via dye tracing and residue analysis, indicating a strong correlation between uniform suspension application and seed surface coverage. These findings contribute to enhancing treatment efficiency and reducing chemical loss, supporting sustainable and cost-effective agricultural practices.
Keywords: Karakul sheep, lambs, homogenous and heterogenous mating, forms of offspring, picture of location of flowers, length, wool fiber length, durability of flowers, wool-fiber quality.